METAPHORS IN PANTUN FOR WEDDING CEREMONY IN MALAY LANGKAT TRADITION - Afrida . Hanum; Anni Holila Pulungan; Siti Aisyah Ginting (LINGUISTIK TERAPAN, 2022)
Pantun is a old poetry of Malay which is used as a means of delivering ideas, attitude, and cultural values (Sri, 2010:6). Along the ceremony of Malaynese Wedding, there are a lot of clauses that are used to express the speaker’s ideas that implies hopes and suggestions to the people. Next, the words of Pantun are also used to express the speaker’s attitude towards the marriage like to entertaint the bride and groom. In addition to delivering ideas and attitudes. Pantun is also used to present the cultural values of Malay that keep the kinship among family members. Words arranged in Pantun in terms of poetic values contain philosophical of life, politeness ethics, laws and society. Malaynese is a closed society to say something cannot be directly but must be coated with words that make its meaning disguised but easy to understand. The purpose of this study is to explain the use of metaphor types in Pantun for Wedding Ceremony in Malay Langkat tradition. The use of metaphor of this study divided into four, like: information function, expressive function, directive funtion, fatigue funtion. This study used descriptive qualitative research. The data of this study were collected from clauses in pantun that reflected metaphor. The realization of metaphors in pantun were especially existed in Hempang pintu, Hempang kipas, and Hempang batang. The result of this study showed that there were expressive function was 16 (53%), information function was 9 (30%), directive funtion was 4 (13%), and fatigue funtion was 1 (4%). Keywords: Metaphor, Pantun, Culture,  Malay Wedding Ceremony